A SYNTACTIC ANALYSIS OF REDUCED CLAUSES IN THE JAKARTA POSTâ€™S HEADLINES - Pahrul Hadi, M Zaki (Humanitatis : Journal of Language and Literature, 2018)
This study is a qualitative research on reduced clause entitled â€ A Syntactic Analysis of Reduced Clauses In The Jakarta Postâ€™s Headlinesâ€. It answers the types and functions of reduced clauses in the Jakarta post headlines, aiming at finding their types and functions. Data of this research are qualitative in type and sentence containing reduced clauses taken from the Jakarta post. In gathering the data, this research used metode simak (observing method). Extralingual method was used to analyze the data to find out the principles or rules of reduced clause types and functions. In displaying data, informal method was used because of ordinary word usage. This research shows that the Jakarta postâ€™s headlines reduced clauses are three types namely present and past participle, infinitive, and appositive. Present participle usually indicates an active sentence, while past participle usually indicates the passive sentence. The reduced clause in participle form is the result of reduced adjective and adverbial clauses. Infinitive which is the result of reduced noun clause may be interpreted as adverbial of purpose or as adjectival. It consists of the complement that remains after relative pronoun and form of be are omitted. Reduced clauses in the Jakarta postâ€™s headlines have three functions namely a modifier, an adverb, and a noun. The function of reduced clause is equivalent to the function of clause itself. Reduced adjective clause serve as an adjective clause to modify noun, reduced adverbial clause serve as adverbial and to modify the verb of the main clause.